Association between patterns of sedentary time and academic performance in adolescents: the mediating role of self-concept - Bueno, Maria Raquel De Oliveira; Werneck, Andre de Oliveira; Silva, Danilo Rodrigues Pereira da; Oyeyemi, Adewale Luqman; Zambrin, Lidyane Ferreira; Fernandes, Romulo Araujo [UNESP]; Serassuelo, Helio; Romanzini, Marcelo; Ronque, Enio Ricardo Vaz (FapUNIFESP (SciELO), 2022)
Objective: To analyze the association between the pattern of sedentary time (bouts and breaks) with academic performance, with an emphasis on the mediating role of self-concept. Methods: Participants in the cross-sectional study were 394 adolescents (208 girls), aged 10-14 years, from sixth grade from Londrina, Paraná, Brazil. The sedentary time pattern was measured through accelerometry. Definitions: sedentary bouts - uninterrupted periods of sedentary behavior; breaks - nonsedentary period between two sedentary bouts. The self-concept was estimated using the Piers-Harris II Inventory. Academic performance was obtained by school grades. Results: Short sedentary bouts were associated with higher academic performance in boys (1-4 minutes: β=0.035, p=0.007) and girls (1-4 minutes: β=0.031, p=0.014; 5-14 minutes: β=0.054, p=0.001). Long bouts (30 minutes) were associated with lower academic performance in boys (β=-0.023; p=0.011) and girls (β=-0.032; p<0.001). For girls, total and intellectual self-concept mediated the association between all sedentary pattern and academic performance (bouts 1-4 minutes [total: 39% and intellectual: 42.8%]; bouts 5-14 minutes [total: 21.5% and intellectual: 35.4%]; bouts ≥30 minutes [total: 22.6% and intellectual: 32.3%]; and breaks [total: 38.9% and intellectual: 40.7%]). For boys, the total (56.4%) and intellectual (82.9%) selfconcept mediated only the association between bouts of 5-14 minute and academic performance. Conclusions: The pattern of sedentary time is associated with academic performance in adolescents and this association is mediated by self-concept, especially in girls.
Keywords: Academic performance; Adolescent; Sedentary behavior; Self concept